Reciclaje arquitectónico para la atención a migrantes en situación de calle en el Valle del Cauca. (2024)
This architectural approach research focused on analyzing the viability and need to create a care center for homeless migrants and displaced people in Valle del Cauca, through architectural recycling. An exhaustive field study was carried out, using ethnographic analysis.